Modeling the magnetic properties of DyFe2/YFe2 superlattices - Bowden, G; Beaujour, J; Zhukov, A; Rainford, B; de Groot, P; Ward, R; Wells, MR (2003)
The Stoner-Wohlfarth model, adapted to include magnetic exchange springs, was used to study coercivities of antiferromagnetically coupled DyFe2/YFe2 multilayer films. It was observed that coercivity rises sharply as the net magnetic moment of the superlattice approaches zero. A computational model was developed to explain the bending field, signifying the onset of a magnetic exchange spring, and the irreversible switching field, associated with magnetic reversal.